2011
DOI: 10.1017/s1355617711000877
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Depressive Symptoms and Semantic Memory in Amnestic Mild Cognitive Impairment and in Late-Life Depression

Abstract: Semantic deficits have been documented in the prodromal phase of Alzheimer's disease, but it is unclear whether these deficits are associated with non-cognitive manifestations. For instance, recent evidence indicates that cognitive deficits in elders with amnestic mild cognitive impairment (aMCI) are modulated by concomitant depressive symptoms. The purposes of this study were to (i) investigate if semantic memory impairment in aMCI is modulated according to the presence (aMCI-D group) or absence (aMCI group) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 39 publications
6
33
2
4
Order By: Relevance
“…In patients with dementia, impairments on these tests were found in 49% for the most frequently impaired test (‘Naming of famous faces') and in 38% for the least commonly impaired test (‘Category fluency'). The findings here are supported by previous studies, which show that semantic memory deficits are found in many patients with dementia, and that such deficits may be found in MCI [13,14,16,17]. …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In patients with dementia, impairments on these tests were found in 49% for the most frequently impaired test (‘Naming of famous faces') and in 38% for the least commonly impaired test (‘Category fluency'). The findings here are supported by previous studies, which show that semantic memory deficits are found in many patients with dementia, and that such deficits may be found in MCI [13,14,16,17]. …”
Section: Discussionsupporting
confidence: 92%
“…Other studies have shown that not only faces but also names for famous buildings are particularly prone to impairment in aMCI [16]. The results demonstrate that deficits on tests relying heavily on semantic memory are found in many patients with dementia, and even that such deficits may also be found in MCI (both in aMCI and non-aMCI) [13,14,16,17]. In patients with dementia, impairments on these tests were found in 49% for the most frequently impaired test (‘Naming of famous faces') and in 38% for the least commonly impaired test (‘Category fluency').…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Distributional approaches may introduce additional noise into the computation of semantic indices resulting in more variability in measurements and, thus, would need to be further validated. The analysis presented in this manuscript does not take into account depression as a concomitant condition with dementia that may also affect semantic memory and SVF performance (Brunet et al, 2011; Callahan et al, 2015; Klumpp et al, 2010). We plan to investigate effects of depression in future work.…”
Section: Limitationsmentioning
confidence: 99%
“…Although conventional naming tests provide more information on the maximum naming accuracy rates, our naming test may better reflect the difficulty encountered in naming in real-life situations. It may also compensate for the ceiling effect observed in patients with MCI without comorbid depression [50], while still using the short naming assessment tool that is widely used in current clinical settings. Combining naming tests with evaluation using hallmark neuropsychological deficits may facilitate a more efficient and specific diagnosis of MCI.…”
Section: Discussionmentioning
confidence: 99%